Schiffman, Lawrence; Swartz, Michael D. Hebrew and Aramaic Incantation texts from the Cairo Genizah. Selected textfrom the Cairo Genizah. - Torijano, Pablo A. ('Ilu. Revista de Ciencias de las Religiones, 1998)
Sin resumen